Simulation research to enhance patient safety and outcomes: recommendations of the Simnovate Patient Safety Domain Group. (24th March 2017) - Pucher, Philip H; Tamblyn, Robyn; Boorman, Daniel; Dixon-Woods, Mary; Donaldson, Liam; Draycott, Tim; Forster, Alan; Nadkarni, Vinay; Power, Chris; Sevdalis, Nick; Aggarwal, Rajesh
Abstract : The use of simulation-based training has established itself in healthcare but its implementation has been varied and mostly limited to technical and non-technical skills training. This article discusses the possibilities of the use of simulation as part of an overarching approach to improving patient safety, and represents the views of the Simnovate Patient Safety Domain Group, an international multidisciplinary expert group dedicated to the improvement of patient safety. The application and integration of simulation into the various facets of a learning healthcare system is discussed, with reference to relevant literature and the different modalities of simulation which may be employed. The selection and standardisation of outcomes is highlighted as a key goal if the evidence base for simulation-based patient safety interventions is to be strengthened. This may be achieved through the establishment of standardised reporting criteria. If such safety interventions can be proven to be effective, financial incentives are likely to be necessary to promote their uptake, with the intention that up-front cost to payers or insurers be recouped in the longer term but reductions in complications and lengths of stay.